Primary Care Group Visits for Childhood Obesity: Clinical Program Evaluation. (April 2018) - Bottino, Clement J.; Puente, Gabriella C.; Burrage, Amanda; Tannis, Candace; Cheng, Jennifer K.; Epee-Bounya, Alexandra; Cox, Joanne E.
We conducted 29 group visits targeting children with elevated body mass index (BMI) and their families. Visit activities focused on social support, mind-body techniques, exercise, and nutrition. Measures included attendance, family satisfaction scores, and per-patient change in BMI percentile. Ninety-six patients attended ≥1 group visit, mean 2.0 (SD ±1.8; range 1-14). Mean patient age was 9.6 years (SD ±2.4; range 4-15 years); 53.1% were female; 44.8% had a BMI 95th to 99th percentile for age/sex; 35.4% had a BMI >99th percentile. Mean attendance per group visit was 6.8 patients (SD ±3.8; range 1-16 patients). Mean family satisfaction scores were 9.8 (SD ±0.8) with 10/10 "would recommend to family or friends." Of 42 patients who attended ≥2 group visits, 5 (11.9%) experienced a ≥5 BMI percentile reduction between first and last visits; 3 (7.1%) maintained this reduction 2 years later. Group visits were associated with high family satisfaction scores, though few patients experienced a reduction in BMI percentile.